AN ANALYSIS OF SCIENTIFIC APPROACH IN TEACHING ENGLISH AT SMA NEGERI 6 MEDAN - Khairunnisa Fitri Nasution; Tiarnita Maria Sarjani Siregar; Puan Suri Mira Annisa Sembiring (Universitas Negeri Medan, 2020)
This study was about an analysis of Scientific Approach in teaching English classroom. The aimed of this study were (a) to analyze the implementation of the five scientific approach in English language teaching, and (b) to find out how the teachers comprehend the concept of Scientific Approach. The subject of this research were the English teachers of SMA NEGERI 6 MEDAN. This research used descriptive qualitative research. To answer the problems of the study, the data were collected in three ways by observing, recording, and interviewing. The data were analyzed based on Miles and Huberman (1994). The result of this study were the following, (a) the first teacher was implement the observing, experimenting, and communicating process. The second teacher was implement the experimenting, associating, and communicating process. The teachers have not implemented all the five stages of Scientific Approach, (b) it found that the teachers showed lack of comprehension relating to the concept of Scientific Approach.Keywords: Scientific Approach, 2013 Curriculum, Implementation.